Trade Finance by Islamic Banks and Exchange Rates: A Study of Pakistan's Exports between 2010-2022 - Umair Khan; Muhammad Muzammil, (South Asian Review of Business and Administrative Studies (SABAS), 2023)
This study examines the factors that can affect the Exports of Pakistan, by paying particular attention to letter of credit financing by Islamic banks in Pakistan and exchange rate. Sample data of Islamic listed Banks is selected from last twelve years i.e. 2010 to 2022 with 975 observations. Study measures export performance using exports figures of Pakistan as the proxy for export performance while external factors namely letter of credit financing by Islamic banks and exchange rate used as an influencing factor. Applying panel data analysis, the results provide positive association Pakistan’s export with Islamic banks' letter of credit financing and exchange rate, indicating that easy availability of trade financing and favorable exchange rate can help increase Pakistan’s exports. The findings can aid policy managers, banking professionals, particularly those hoping to boost exports and foreign exchange through them. The study may also benefit managers seeking to broaden their knowledge of the key elements influencing export performance.